The Effect Of Social Support On Purchase Intention With Consumer Trust As A Mediating Variable Study On Consumers Tiktok Shop Bandar Lampung City - Annisa Tri Widya; Febrian Eko Saputra (SEAN Institute, 2024)
The purpose of this study was to analyze and discuss social support on purchase intention with consumer confidence as a mediating variable for TikTok Shop consumers in Bandar Lampung City. This study uses a quantitative approach using a questionnaire for data collection. The population in this study were people in Bandar Lampung City who had made purchases through TikTok Shop. Because accurate data has not been found regarding the people of Bandar Lampung city who have made purchases through TikTok Shop, this study uses a non-probability sampling method with the sampling technique, namely purposive sampling (sampling through specific criteria and characteristics). Non-probability sampling is used with the target of the people of Bandar Lampung city who have made purchases through TikTok Shop. Data analysis was carried out using Structural Equation Modeling (SEM) Partial Least Square (PLS). The results showed that social support has a significant effect on purchase intention through consumer trust at TikTok Shop in Bandar Lampung City. Social support affects consumer trust. Trust affects purchase intention. Social support affects purchase intention. Trust mediates social support on purchase intention.